2014
DOI: 10.4236/cs.2014.511029
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Signal Processing Coprocessor for <i>n-</i>Dimensional Geometric Algebra Applications

Abstract: This paper provides an implementation of a novel signal processing co-processor using a Geometric Algebra technique tailored for fast and complex geometric calculations in multiple dimensions. This is the first hardware implementation of Geometric Algebra to specifically address the issue of scalability to multiple (1 -8) dimensions. This paper presents a detailed description of the implementation, with a particular focus on the techniques of optimization used to improve performance.Results are presented which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Table 2 gives a comparison for different dimensions, GA processor performance in MHz, clock cycles, latency and Geometric Operations per Second (GOPS). This also provides a comparison to the GA hardware implementations in [21,23,[25][26][27][28][29][30]. It was found that the proposed hardware is an order of magnitude faster as shown in Table 2 (columns 5-6).…”
Section: Comparison With Other Ga Implementation Hardware and Softwarementioning
confidence: 93%
See 3 more Smart Citations
“…Table 2 gives a comparison for different dimensions, GA processor performance in MHz, clock cycles, latency and Geometric Operations per Second (GOPS). This also provides a comparison to the GA hardware implementations in [21,23,[25][26][27][28][29][30]. It was found that the proposed hardware is an order of magnitude faster as shown in Table 2 (columns 5-6).…”
Section: Comparison With Other Ga Implementation Hardware and Softwarementioning
confidence: 93%
“…From an implementation perspective, these functions can also be decomposed into parallelized tasks, each task involving Multiply and Accumulation (MAC) operations, which can map directly to specific hardware. It is already known that significant speed advantages can be gained when GA is implemented in hardware instead of software [21][22][23]. The hardware architecture is discussed in this section, however, a detailed description is beyond the scope of this paper, and the reader is referred to [23] for more information.…”
Section: Rotor Edge Detection Using Geometric Algebra Co-processormentioning
confidence: 99%
See 2 more Smart Citations